Daily activity avoidance in the context of urinary and fecal incontinence among young adults with Spina Bifida: Preliminary results from an ecological momentary assessment study - Devon J. Hensel; Audrey I. Young; Konrad M. Szymanski (PLoS ONE, 2026)
Although studies suggest that young adults with spina bifida (YASB) often avoid important daily activities (ADL) due to urinary (UI) and fecal (FI) incontinence, no research has prospectively examined how often ADL avoidance occurs, or the context in which it occurs. In this paper, we used ecological momentary assessment (EMA) over 30 days to describe: 1) the frequency of avoidance; 2) the activities YASB most commonly avoid; and 3) preliminary association of daily avoidance with affect, incontinence anxiety and health-related quality of life (HRQoL). As part of a larger 30-day prospective study designed to understand the incontinence in adults with SB (N = 89), participants completed an end-of-day EMA tracking daily ADL avoidance on days when they were worried about possible UI or FI and on days when they had actual UI or FI. Additional day-level measures were: affect and incontinence anxiety. HRQoL was reported in beginning- and end-of-study surveys. We drew a subsample of YASB participants (18–27 years; N = 23 of total 88 participants). ADL avoidance was most frequent with actual FI (20.5%) and least frequent with worry about FI (3.5%, p = 0.02) (UI worry: 8.3; actual UI: 8.9%, p = 0.546). The most common ADL avoided were eating, drinking and spending time with family/friends. Negative mood and incontinence anxiety were significantly higher on days with all types of avoidance. Higher baseline HRQoL was associated with fewer in-study ADLs avoided, which were in turn associated with higher end-of-study HRQoL. Our data suggest that YASB avoid key activities of daily living (e.g., eating, drinking, seeing family/friends) both when they worry about possible incontinence that may but does not occur, and when they experience actual incontinence. Tailored interventions addressing actual incontinence and worry about possible incontinence incorporating daily mood or incontinence anxiety may minimize ADL avoidance and its impact on long-term HRQoL.